Development of an inservice program on phonemic awareness for teachers and early chlldhood educators - Bursey, Kim (Kimberley Joy), 1967- (1997)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1998. Education Bibliography: leaves 226-230 This thesis reviews the research on Phonemic Awareness and Inservice Training Programs and culminates in the development of an Inservice Program on Phonemic Awareness. The research on phonemic awareness reviewed studies dealing with the correlation between phonemic awareness and reading, the predictive ability of phonemic awareness on reading ability, the effect of training in phonemic awareness skills on reading achievement and the levels of phonemic awareness. The research on inservice training programs reviewed studies dealing with different types of inservice programs, characteristics of effective inservice programs, and some models of staff development. -- An inservice training program was developed for teachers and early childhood educators. The inservice is comprised of four two-hour sessions, designed to be presented over a period of three months. The inservice participants are required to read supplemental articles between sessions, observe their peers using the strategies discussed in the training sessions either in person or through videotape , and administer an assessment to their students both before and at the end of the inservice. The facilitator is required to provide videotapes of several of the activities being used with children and is encouraged to provide examples of some of the activities to show the participants. Definitions and theoretical background are provided for both the facilitator and the participants. An evaluation of the inservice is provided for the participants to complete at the end of the inservice training program.